Factors affecting turnover intention among employees in hotel industry: a study on Langkawi Island, Malaysia - Seffar, Walid (2020)
The primary purpose of this study was to investigate the effect of authentic leadership, workload, organisational trust, employee engagement, communication climate and turnover intention among hotel industry employees in Langkawi island. A total of 360 Questionnaires were distributed to employees working in the hotel industry in Langkawi island. A total of 210 questionnaires were returned but only 191 were used in the analysis using Structural Equation Modelling (SEM) - Partial Least (PLS) method. The results of the study revealed a significant effect of workload, organisational trust, and communication climate on turnover intention. The results also revealed an insignificant effect of authentic leadership and employee engagement on turnover intention. The present study also highlighted the implications of the research, future research recommendations as well as its limitations.